2010
DOI: 10.4028/www.scientific.net/kem.452-453.525
|View full text |Cite
|
Sign up to set email alerts
|

Experiment Research of Environment Effects on Fatigue Life of Carbon/Bismaleimide Composite Laminates with Central Hole

Abstract: The effects of humidity and ultraviolet radiation aging on fatigue properties of carbon/ bismaleimide composites and coating protection action were presented. Specimens with central hole are made of carbon/bismaleimide laminates. Compression-compression (C-C) fatigue tests under normal lab environment were operated respectively for four groups of specimen, (1) specimen under normal lab environment, (2) specimen under UV radiation aging with dryness, (3) specimen under UV radiation aging with moisture, and (4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Depositing metal like aluminum may be a solution to this problem as aluminum itself has got a large application in aircraft industry. AFM topography of metal /BMI/Mild steel is shown in fig 10. The scanning area was 50 µm × 50 µm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Depositing metal like aluminum may be a solution to this problem as aluminum itself has got a large application in aircraft industry. AFM topography of metal /BMI/Mild steel is shown in fig 10. The scanning area was 50 µm × 50 µm.…”
Section: Resultsmentioning
confidence: 99%
“…Thin ceramic coatings Silica coatings has been deposited on bismaleimide (BMI) polymeric substrates as reinforcements or extenders and their Vickers microindentation has been performed which showed cracking [5,6].Siliconized epoxy-phosphorus based bismaleimide coating systems using diglycidylether terminated poly (dimethylsiloxane) (DGTPDMS) and phosphorus-containing bismaleimide (PBMI) as chemical modifiers for epoxy resin has been developed [7].BMI is used to improve the thermomechanical properties of the parent resin [8]. It has been also used for making UV-curable hybrid coatings [9].Studies have also been made on the Environment Effects on Fatigue Life of Carbon/BMI Composite Laminates [10]. Patents have also been filled where BMI coatings have shown potential as a corrosion protection polymer for metals used in vehicles [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As low weight has become one of the most urgent targets for both vehicles and airplanes in meeting customer demands and government regulations for energy efficiency, the situation can be improved with the implementation of CFRP composites because of their many advantages in terms of high strength-to-density ratio and good fatigue resistance. The complexity derives from different failure mechanisms, which are influenced by several factors according to previous studies: (1) mechanical properties of the material components, such as fibre, matrix, and fibre-matrix interface 11 ; (2) fibre orientation and fibre volume fraction 12,13 ; and (3) manufacturing defects and material aging due to the extreme working conditions (eg, fibre defects, 14 voids, [1][2][3][4][5][6][7][8][9][10] and mechanical degradation due to hygrothermal aging 15 or ultraviolet radiation 16 ). i, sample after n, cycles; [σ t ], = tensile strength; [σ c ], = compressive strength; a, = normalized stress amplitude; q, = normalized mean stress; c, = ratio between compressive strength and tensile strength; A, f, = constants associated with material; γ(v v ), = intercept of S − N, curve with vertical axis (for composite with void content of v v , ); k(v v ), = slope of S − N, curve (for composite with void content of v v , ); σ max , σ min , = maximum and minimum stress of cyclic load; D, = fatigue damage index; E 0 , = initial modulus; E(N), = residual modulus of the N th , cycle; E(N f ), = modulus at final fracture; δ(u, v v ), φ i (u, v v ), = functions related to the characteristics of damage accumulation (i∈, 1,2) done to investigate the mechanical properties of polymer composites; however, some of the work revealed that the voids have an impact on the mechanical properties, especially fatigue performance.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] It has been commonly accepted that the fatigue process of composites is totally different and more complicated compared with that of metals. The complexity derives from different failure mechanisms, which are influenced by several factors according to previous studies: (1) mechanical properties of the material components, such as fibre, matrix, and fibre-matrix interface 11 ; (2) fibre orientation and fibre volume fraction 12,13 ; and (3) manufacturing defects and material aging due to the extreme working conditions (eg, fibre defects, 14 voids, [1][2][3][4][5][6][7][8][9][10] and mechanical degradation due to hygrothermal aging 15 or ultraviolet radiation 16 ). Among these factors, voids, as one of the most common defects in resin polymer composites, are inevitably induced during manufacturing process.…”
Section: Introductionmentioning
confidence: 99%